Parametric Dependence of the Formation of Electron Butterfly Pitch Angle Distribution Driven by Magnetosonic Waves. Issue 10 (21st October 2020) - Zhou, Ruoxian; Fu, Song; Ni, Binbin; Hua, Man; Yi, Juan; Gu, Xudong; Hu, Zejun; Cao, Xing; Xiang, Zheng; Wang, Qi; Ma, Xin; Wang, Jingzhi; et al.
Abstract: Using the full relativistic test particle (TP) simulation code, we investigate the parametric dependence of electron scattering and phase space density evolution driven by magnetosonic (MS) waves at L = 4.5 both inside and outside the plasmapause. The scattering effects caused by Landau resonance, bounce resonance, and the transit‐time effect are all involved in the study. The net scattering effects are evaluated in the form of diffusion coefficients with different combinations of MS wave parameters, such as frequency bandwidth and wave normal angle, and ambient plasma density. The results demonstrate that (1) Landau resonance and the transit‐time effect dominate the electron scattering inside and outside the plasmapause, respectively, while both are modulated by bounce resonant scattering; (2) bounce resonant scattering becomes more important with narrowband MS waves; (3) electron scattering induced by MS waves is highly sensitive to wave normal angle. The temporal phase space density (PSD) evolution obtained from 2‐D kinetic Fokker‐Planck simulations shows that MS waves with larger wave normal angles are more likely to generate electron butterfly pitch angle distributions (PADs) for hundreds of keV electrons outside the plasmapause. Our study suggests that the electron butterfly distribution has important implications for revealing the combined scattering of MS wave‐particle interactions, and the combination of the multiple scattering mechanisms should be carefully incorporated in future global modeling of radiation belt dynamics. Key Points: The transit‐time effect with bounce resonance by MS waves dominates the electron scattering outside the plasmapause Electron scattering by MS waves is sensitive to frequency bandwidth, wave normal angle, and plasma density MS waves generate electron butterfly pitch angle distributions more efficiently outside the plasmapause